The nightingale gallery - Doherty, P. C. (Harding, Paul, 1946- Sorrowful mysteries of Brother Athelstan, 2022)
"In 1376, the Black Prince dies of a terrible sickness, closely followed by his father, King Edward III in 1377. Nobles and merchant Princes gather like wolves around the empty throne, and one of them, Sir Thomas Springall, is murdered within a few days of the old king's death. Sir John Cranston, the coroner of London, is ordered to investigate. He is assisted by Brother Athelstan, a Dominican monk. Soon enough, they are drawn into a dark and terrifying web of intrigue."-- Provided by publisher.